A Comparative Approach on Scheduling Algorithms for Real time Systems - Manasa R; Divya Mabbu (Journal Electrical and Computer Experiences, 2023)
Real-time systems are extensively used in many applications, especially critical systems. A real-time system is considered to be reliable and safe if it is able to execute all its tasks accurately within given time constraints. A requirement might need the real-time systems to execute several tasks. The system must be able to assign processors and necessary resources to ensure smooth and timely execution. In this paper, we give an overview of existing scheduling algorithms for static and dynamic systems. This paper also presents a comparative study of these scheduling algorithms.